The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/mou.0b013e3283383b02
|View full text |Cite
|
Sign up to set email alerts
|

Current state of penile rehabilitation after radical prostatectomy

Abstract: This review will evaluate the current theories of the cause of postprostatectomy erectile dysfunction, alterations in surgical technique to minimize it, and the application of erectogenic pharmaceuticals to improve recovery of erectile function, or maximize its preservation. A discussion of basic science evidence and clinical trials will be reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…IIEF data however suggests continued improvements up through the completion of this trial at 13 months. Prior studies reported that recovery can occur up to 24–40 months following surgery and several authors suggest a treatment course of up to 24 months (Mulhall, ; Garcia & Brock, ). Longer follow‐up would be needed to assess long‐term recovery on RigiScan ™ with PDE5i therapy in this study.…”
Section: Discussionmentioning
confidence: 99%
“…IIEF data however suggests continued improvements up through the completion of this trial at 13 months. Prior studies reported that recovery can occur up to 24–40 months following surgery and several authors suggest a treatment course of up to 24 months (Mulhall, ; Garcia & Brock, ). Longer follow‐up would be needed to assess long‐term recovery on RigiScan ™ with PDE5i therapy in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this trial did not support nightly PDE5 inhibitors over on‐demand dosing, and in fact found no improvement in EF after washout for either protocol compared with placebo. This impressive REINVENT trial was also subject to some limitations . The overall design was complicated, with three arms and participant‐controlled titration of dosing, which muddied the analysis .…”
Section: Discussionmentioning
confidence: 99%
“…This impressive REINVENT trial was also subject to some limitations . The overall design was complicated, with three arms and participant‐controlled titration of dosing, which muddied the analysis . Drop‐out rates were high, ranging between 31 and 35% in the study arms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there have been advances in our understanding of the pathophysiology of post‐RP ED. These include the introduction of management protocols in the postoperative period and the identification of factors that allow us to predict which patients will most likely have return of normal EF (Penson et al, 2003; Dubbelman et al, 2006; Garcia and Brock, 2010; Kim et al, 2011; Treiyer et al, 2011).…”
Section: Edmentioning
confidence: 99%